Management of Infected Calcific Myonecrosis: A Report of 2 Cases - Nagano, Hisato (Plast Reconstr Surg Glob Open, 2020)
Calcific myonecrosis (CM) is a rare condition in which a large calcified mass develops after trauma. Generally, CM occurs in a lower extremity, and there have been no reports of its occurrence in the upper arm. We report 2 cases of infected CM, including a rare case of CM occurrence in the arm and a typical case in the leg. Case 1: An 84-year-old woman presented with a draining sinus and a large calcified mass in the arm and axillary region. The mass involved the neurovascular bundle; thus, complete resection was impossible. We performed surgical debridement and postoperative negative-pressure wound therapy with instillation and dwell. Case 2: A 43-year-old man presented with a large calcified mass in the right leg and 2 draining sinuses. After surgical debridement, negative-pressure wound therapy was initiated. However, the wound became infected, and we performed additional debridement, followed by a split thickness skin grafting. The infection was controlled in both patients, although complete resection was not feasible. Complete resection is generally considered the optimum treatment for infected CM, but it is difficult to achieve in some patients. Negative-pressure wound therapy with instillation and dwell appears as a good option for postoperative management if complete resection of infected CM cannot be achieved.